0403 Sleep Valuation: A Novel Construct and Questionnaire. (27th May 2020) - Nielson, S; Simmons, Z; Kay, D
Abstract: Introduction: Sleep valuation, the relative worth of one's own sleep, is an under-explored construct that could have implications on sleep health. This study sought to validate the Sleep Valuation Questionnaire (SVQ) and to explore demographic differences in sleep valuation. Methods: Participants ( N = 946) recruited through TurkPrime were stratified across age (18-99), race (50% White, 17% Black, and 8.33% for each American Indian, Asian, Pacific Islander, and other), Hispanic ethnicity (20%), gender (50/50 female/male), employment status (50% employed full time and 8.33% for each part time, homemaker, retired, student, temp worker. unemployed, and disabled), Participants completed a demographic survey, followed by the original 43 item SVQ completed twice. Iterated principal factoring with a Promax solution was used to identify the factor structure of the SVQ. Cronbach's alpha and correlation analyses were also used to help identify items with poor reliability. Total sleep valuation, the sum of valid items on the SVQ, was used as the dependent variable in a multiple regression analysis. Age, gender, race, work status, socioeconomic status, educational level, marital status, and general health and mental health estimates served as independent variables. Results: After removing items with weak factor loadings (<0.6), poor reliability, and weak face validity, the number of items were reduced to 10, which loaded on to 2 factors: Sleep Desire and Sleep Need. Those who cohabitate had lower SVQ scores than married individuals ( p =0.04), full-time workers had higher SVQ scores than non-full-time workers ( p =0.001), higher age was associated with lower SVQ scores ( p <0.001), and higher general mental health was associated with lower SVQ scores ( p <0.001). Conclusion: This is the first study to explore how demographic variables relate to sleep valuation. The SVQ may help identify factors that contribute to sleep valuation and sleep valuation relates to sleep behavior, sleep health, and sleep treatment utilization. Support: None